Development of a required longitudinal residency experience focused on deprescribing. (21st January 2019) - Pruskowski, Jennifer; Sakely, Heather; Handler, Steven
Abstract: Purpose: In this article we describe a novel required longitudinal experience focused on deprescribing designed for postgraduate year 2 (PGY2) geriatric pharmacy residents. This experience was embedded within a clinical pharmacist–driven deprescribing service. Insights on challenges faced and benefits gained during the first offering are also highlighted. Summary: Through collaboration with the University of Pittsburgh School of Pharmacy (UPMC) Palliative and Supportive Institute and the UPMC St. Margaret PGY2 geriatric pharmacy residency program, a year-long required deprescribing-focused experience was developed and executed. The experience was aligned with the American Society of Health-System Pharmacists' standard goals and objectives and was designed to focus and evaluate 3 skills necessary for all pharmacy practitioners: empathy, critical thinking, and communication. There is a need for proactive deprescribing initiatives to reduce the unnecessary burden and cost associated with potentially inappropriate medications for older patients. Focused deprescribing experiences can better equip pharmacist learners with the ability to lead these initiatives. Conclusion: A required longitudinal deprescribing-focused experience can provide PGY2 geriatric pharmacy residents with opportunities to practice empathy, critical thinking, and communication beyond those typically offered in a residency program.